DETERMINAN FINANCIAL DISTRESS DENGAN KOMITE AUDIT SEBAGAI PEMODERASI - Fadhilah, Khairul; Prastowo Darminto, Dwi; Ahmar, Nurmala (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
The main objective of this study is to determine the effect of Return on Assets, Current Ratio and Debt to Equity Ratio on financial distress moderated by the Audit Committee. The analysis in this study uses the Zmijewski model. The data used in this study is secondary data derived from annual reports of companies in the Basic Industry and Chemical Sector which are listed on the Indonesia Stock Exchange for the 2016-2020 period. The results showed that the return on assets and current ratios have a negative effect on financial distress, while the debt to equity ratio has a positive effect on alpha 10%. The Audit Committee has no effect on financial distress. The Audit Committee can moderate the effect of the debt to equity ratio on financial distress. Meanwhile, the effect of the current ratio on financial distress cannot be moderated by the audit committee. Keywords: Financial Distress, Current Ratio, Debt to Equity Ratio, Return on Assets, Audit Committee